Behavioural assessment impacts on the performance results - Patrício, Rita Sofia Diniz (2010)
This study examines the relationship between the behaviours assessed in a performance management system and the performed results achieved by the employees. It also studies the interdependency among the different behaviours assessed to the workers. The quantitative research used statistical methods such as: correlation matrix, factorial analysis, and multiple and simple regression methodologies. A sample of N=129, was collected from the data base of a bank institution's commercial department in order to acquire the results of the performance assessment. The results were quite enlightening as they show a strong relationship among the competences assessed. It also shows that only few of them are related with the performance results. The factorial analysis output shows an unique factor which explains more than 73% of the different competences' total variances assessed by the performance management. The performance results do not demonstrate a relation with all the assessed behaviours. Even though, some of them jointly, generate an impact on the performance results, which is demonstrated by a multiple regression analysis.